Cost Effectiveness of Newborn Hearing Screening Protocol in Reduction of Refer Newborn Hearing Loss for Diagnosis - Chindavijak, Somjin; Tanamai, Napas; Khongsaksri, Aroonwan; Withyapraphaiphan, Saranya; Khitchaidiao, Atcharaphorn; Susonthitaphong, Ruthai; Chao-amonpat, Suwanna; Boonmee, Supranee; Khemvaranan, Chalida; Thaiyakul, Arunee (Journal of The Department of Medical Services, 2022)
Background: The high efficiency newborn hearing screening program that decrease the abnormal hearing screening result newborns will reduce the problem of referral system for diagnosis because lack of audiologist in each health region. Objective: To study cost - effectiveness between newborn hearing screening with Automated Auditory Brainstem Response (AABR) when Otoacoustic Emission (OAE) unpass (AABR + OAE when OAE unpass) to reduce refer rate for diagnostic test to OAE alone program. Method: Data from newborn hearing screening in Rajavithi Hospital during Oct 1st 2019 to Sep 30th 2020 were used to assess the cost - effectiveness of AABR when OAE unpass. The data of OAE alone in Rajavithi Hospital was previously reported in 2011. The model based cost-effectiveness analysis were conducted and limited at the time to diagnostic test with horizontal time frame 1 year without reduction rate. All the cost for screening include all societal perspective which were indirect and direct cost whether by hospital and family. The outcome measure of the economic analysis was the cost per case of decrease refer newborn for diagnosis. In order to reflect uncertainty, deterministic and probabilistic sensitivity analyses were performed. Result: The direct cost of AABR + OAE when OAE unpass was 1016.61 Baht and OAE was 188.71 Baht. The result of total cost which included direct and indirect cost in the protocol of AABR + OAE when OAE unpass was 3,186,461.00 Baht compare to OAE protocol which was 3,314,425.61 Baht per 10,000 newborns hearing screening and the number of refer newborn of AABR + OAE when OAE unpass was 12 compare to 54 newborns for conventional protocol by saving for the cost of 3,044.33 Baht. Conclusions: The protocol of AABR + OAE when OAE unpass decrease refer newborn for diagnosis which decrease of total cost of hearing from screening to diagnosis. And in the area that audiologist was not available, this protocol will be benefit in the term of reduction of refer rate and waiting list for diagnosis.